Sosialisasi Dan Pemahaman Masyarakat Tentang Pembuatan Eco Enzyme Serta Pemanfaatannya Dalam Rumah Tangga - Susana Tabah Trina Sumihar; Nainggolan, Hotden; Elisabeth Sri Pujiastuti; Ferlist Rio Siahaan; Albina Ginting; Yanto Raya Tampubolon (LPPM Universitas HKBP Nommensen, 2024)
This service activity aims to ensure that participants understand the importance of managing household organic waste to overcome environmental problems, increase participants' understanding regarding eco-enzymes and their use in the household; increase participants' understanding regarding the materials used to make eco-enzymes in the household. This counseling was carried out at the Church of HKBP Nommensen Resort Pulu Brayan Medan, to 50 parompuan community (Church Women's Community) of the HKBP Pulu Brayan as participants, then an evaluation was carried out on the 25 participants. The method of this service activity is; socialization by resource persons; discussion and direct practice in making eco-enzymes and evaluation processes. Based on the outreach activities carried out, it was concluded; a) there was an increase in participants' understanding regarding eco-enzymes and their use in the household; b) there was an increase in participants' understanding regarding the materials used to make eco-enzymes in the household; c) socialization and training on making eco enzymes for parompuan community in church of the HKBP Nommensen Pulu Brayan plays a role in increasing participants' knowledge about eco-enzymes and the process of making them, good environmental management, and the use of waste into environmentally friendly products. Based on the conclusions, it is recommended that ongoing outreach activities be carried out and include all members of the church congregation, so that they can utilize organic waste into environmentally friendly products.